The effect of audit opinion, financial distress, and good corporate governance on audit delay - Sugiyanto Sugiyanto (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2022)
This study examines the effect of audit Opinion, financial distress and good corporate governance on audit delay. The population of this study uses mining groups indexed at the Indonesia Stock Exchange for the 2016-2020 period. Sampling approach with purposive sampling technique. The number of samples used in this study was 25 companies in the mining sector for five years—quantitative research. The source of records on this take a look at is secondary records withinside the shape of the company's annual report. The data analysis method used is multiple linear regression analysis. This study shows that financial distress positively affects audit delay. However,  audit opinion and good corporate governance do not affect audit delay.